Strategi Pengelolaan Dampak Lingkungan di PIK Jakarta Utara - Steve Elia Amadeus; Budi Setiawan (Lembaga Pengembangan Kinerja Dosen, 2026)
Pantai Indah Kapuk (PIK) in North Jakarta faces increasing ecological pressure due to coastal reclamation, urban expansion, and intensive tourism activities. This study aims to formulate sustainable environmental management strategies for the PIK area using Strategic Management Theory as the analytical framework. The research employs a systematic literature review of 30 national and international journal articles published between 2023 and 2025 related to coastal environmental management. Data were collected through Google Scholar and analyzed using a thematic approach to identify effective strategic patterns. The findings reveal four main strategies for environmental management in PIK. First, identifying the causes of ecological degradation through the analysis of waste, sedimentation, and changes in coastal vegetation cover. Second, formulating mitigation policies collaboratively by involving the government, private sector, academia, and local communities. Third, implementing programs for waste control, mangrove ecosystem conservation, and energy efficiency through green innovation, environmentally friendly architecture, and community participation. Fourth, ensuring continuous evaluation of policy effectiveness through adaptive spatial monitoring and the application of the Strategic Environmental Assessment (SEA) framework. These four strategies form an integrative and adaptive framework for balancing economic growth with ecological sustainability. Their implementation is expected to position PIK as a model of sustainable urban coastal management in Indonesia.